Efek suplementasi seng terhadap gejala yang berhubungan dengan diare akut ringan pada anak - Boas, Esther (UNIVERSITAS SAM RATULANGI, 2016)
Abstract: Diarrhea is still a serious problem and is one of the factors that led to infant and young children’s deaths in developing countries, including Indonesia. Morbidity (Incidence Rate) diarrhea for all age groups in Lampung from year 2005 to 2012 are likely to rise, from 9.8 per 1000 population to 18.24 per 1000 population in 2012. It is known that zinc plays some important roles in regulation of intestinal fluid transport, maintainance of mucosal integrity, as well as improvement of immunity, gene expression, and oxidative stress. This study aimed to obtain the effect of zinc supplementation on symptoms associated with diarrhea on the seventh day of therapy in puskesmas (primary helath care) Kalianda, South Lampung. This was a randomized control trial study with a cross sectional design. Samples were children with mild acute diarrhea, divided into two groups: zinc group and without zinc group. Patients who showed no more acute diarrhea symptoms within seven days of treatment were determined as recovered. Data were presented in tabular form and analyzed by using the chi-square test. The results showed a total samples of 61 patients with acute mild diarrhea. The highest percentages were as follows: age 4 years old (19.6%), male gender (54.1%), and 2-day duration of diarrhea before admitted to Puskesmas Kalianda (44,26%). The chi-square test showed a significant difference between the two groups (P < 0.001). Conclusion: Supplementation of zinc added to oralit in children with mild acute diarrhea can significantly reduce symptoms of mild acute diarrhea on the seventh day compared to oralit monotherapy.Keywords: acute diarrhea, zinc, oralitAbstrak: Penyakit diare masih menjadi masalah yang serius dan merupakan salah satu faktor yang menyebabkan kematian bayi dan balita di negara berkembang termasuk Indonesia. Angka kesakitan (Incidence Rate) diare untuk semua kelompok usia di Provinsi Lampung dari tahun 2005-2012 cenderung meningkat, yaitu dari 9,8 per 1000 penduduk menjadi 18,24 per 1000 penduduk di tahun 2012. Seng diketahui membantu mengatur transpor cairan intestinal, menjaga integritas mukosa, meningkatkan imunitas, memperbaiki ekspresi gen dan stress oksidatif. Penelitian ini bertujuan untuk mengetahui efek pemberian suplemen seng terhadap penyembuhan dari gejala-gejala yang berhubungan dengan diare pada anak di hari ketujuh terapi di Puskesmas Kalianda, Lampung Selatan. Jenis penelitian ini ialah randomized control trial dengan desain potong lintang. Sampel penelitian ialah pasien anak dengan diare akut ringan yang dibagi menjadi dua kelompok: kelompok seng dan kelompok tanpa seng. Pasien yang menunjukkan hilangnya gejala diare akut dalam tujuh hari pengobatan dinyatakan sembuh. Data yang diperoleh dipresentasikan dalam bentuk tabel dan dianalisis dengan uji Chi-square. Hasil penelitian memperlihatkan terdapat 61 pasien anak sebagai sampel. Persentasi tertinggi diperoleh pada usia 4 tahun (19,6%), jenis kelamin laki-laki (54,1%), dan lama diare sebelum dibawa ke puskesmas ialah 2 hari (44,26%). Hasil uji Chi-square memperlihatkan terdapat perbedaan bermakna antara kedua kelompok (P < 0,001). Simpulan: Pemberian suplementasi seng dan oralit pada anak dengan diare akut dapat menurunkan gejala diare akut ringan secara bermakna pada hari ketujuh dibanding pemberian oralit tunggal.Kata kunci: diare akut, seng, oralit